PHP 7 quick scripting reference - Olsson, Mikael (Web programmer) (Expert's voice in Web development., 2016)
This "pocket" guide reference has been updated with the new PHP 7.0 release. PHP 7 Quick Scripting Reference, Second Edition is a condensed code-rich scripting and syntax reference for the PHP scripting language, the most popular Web scripting language in use today. It presents the essential PHP script in a well-organized format that can be used as a handy reference. What youll learn What is in the new PHP 7 and how to get started with it What are variables, operators, strings, arrays, conditionals, loops and more in scripting setting How to script with functions, class, inheritance, and deal with access levels How to script with static, constants, interface, abstracts, traits How to import files What are Type Hinting and Type Conversions and how to use these in scripting for Web applications How to do variable testing, overloading, sessions What are and how to deal with various scripting for Cookies How to handle namespaces, references, advanced variables, error handling and exception handling.